DEcreased Cognitive functiON, NEurovascular CorrelaTes and myocardial changes in women with a history of pre-eclampsia (DECONNECT): research protocol for a cross-sectional pilot study - Marc E A Spaanderman; Chahinda Ghossein-Doha; Sander MJ van Kuijk; Gwyneth Jansen; Walter H Backes; Emma B N J Janssen; Yentl Brandt; Robert-Jan Alers; Lisanne P W Canjels; Laura M Jorissen; Tamara Michelle Went; Dennis Koehn; et al. (BMJ Open)
Introduction Pre-eclampsia is a hypertensive disorder affecting up to 8% of pregnancies. After pre-eclampsia, women are at increased risk of cognitive problems, and cerebrovascular and cardiovascular disorders. These sequelae could result from microvascular dysfunction persisting after pre-eclampsia. This study will explore differences in cerebral and myocardial microvascular function between women after pre-eclampsia and women after normotensive gestation. We hypothesise that pre-eclampsia alters cerebral and myocardial microvascular functions, which in turn are related to diminished cognitive and cardiac performance.Methods and analysis The cross-sectional ‘DEcreased Cognitive functiON, NEurovascular CorrelaTes and myocardial changes in women with a history of pre-eclampsia’ (DECONNECT) pilot study includes women after pre-eclampsia and controls after normotensive pregnancy between 6 months and 20 years after gestation. We recruit women from the Queen of Hearts study, a study investigating subclinical heart failure after pre-eclampsia. Neuropsychological tests are employed to assess different cognitive domains, including attention, processing speed, and cognitive control. Cerebral images are recorded using a 7 Tesla MRI to assess blood–brain barrier integrity, perfusion, blood flow, functional and structural networks, and anatomical dimensions. Cardiac images are recorded using a 3 Tesla MRI to assess cardiac perfusion, strain, dimensions, mass, and degree of fibrosis. We assess the effect of a history of pre-eclampsia using multivariable regression analyses.Ethics and dissemination This study is approved by the Ethics Committee of Maastricht University Medical Centre (METC azM/UM, NL47252.068.14). Knowledge dissemination will include scientific publications, presentations at conferences and public forums, and social media.Trial registration number NCT02347540.